Pengaruh Kondisi Mahasiswa dan Lingkungan Belajar Terhadap Motivasi Belajar Mahasiswa Administrasi Perkantoran - Sinaga, Very Claudio Fernando; Lestari, Ribi Amelia Citra; Ardila, Dinda Maulida; Jauhara, Ghina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the influence of student conditions and learning environment on the learning motivation of Office Administration Education students at the State University of Medan. The research method used is quantitative. The data analysis technique employed is statistical analysis through hypothesis testing using the T-test. The data collection technique utilized was a questionnaire distributed online, containing relevant questions regarding student conditions, learning environment, and learning motivation. The findings of the study indicate that student conditions and learning environment do not have a significant influence on the learning motivation of Office Administration Education students.